Identification of high-yielding, thermo-insensitive and stable clones of guinea grass (Panicum maximum) - Sukhchain, S; Sidhu, B S (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1988 and 1989 to identify thermo-insensitive and stable clones of guinea grass (Panicum maximum Jacq.). Early-flowering clones were found more thermo-sensitive, showing a sharper decline with the onset of short days and fall in temperature in October. Mean squares due to genotypes and environments were Significant ( P =0.01) for all the 3 characters, green-forage yield, tiller number and plant height, However, mean squares due to genotypes X environment (linear) interactions were significant ( P = 0.01) only for green-forage yield and tiller number. Pooled deviations were non-significant for all these characters. Based on regression analysis and decline (%) in October, only 1 clone, P5 X P9, out of 3 high-yielding clones (P5 X P39, P5 X P9 and P1 X P6), was found stable. All the 4 clones (P20 X P39, P20, P20 X P9 and P6 x P20) showing high mean performance for tiller number were specifically adapted to favourahle growth conditions. Out of all potent clones showing high mean performance for plant height, 2 clones (P1 x P6 and P5 x P31) were found stable.